Measurement and Evaluation of Insulating Properties of a Modified Dielectric Surface using Plasma Discharge - Pernica Roman; Klima Miloš; Fiala Pavel (Measurement Science Review)
Plasma discharges under atmospheric pressure can be used to modify the electrical properties of metallic and dielectric surfaces. The aim of such a modification is to achieve an improvement in the characteristic parameters of the surface, for example in the area of the electrical strength of the surface, in order to achieve a higher ultimate level of electrical breakdown Eb when tested with pulsed or alternating electrical voltages. So far, research has focused on a set of functional experiments carried out using plasma on samples of two types of dielectric materials (thermoset, thermoplastic) with an impact on the final effect of the level of electrical breakdown voltage, electrical intensity and Eb. surface conductivity. The treatment technology requires repeatability and consideration of the industrial deployment conditions of plasma technology. The surface structure was modified in a defined and repeatable way by plasma discharge under atmospheric pressure without the presence of precursors. Methods to evaluate these modifications assessed the change in parameters related to sample type, repeatability and prediction of treatment stability. Subsequently, the surface strength of both the modified samples and the samples not affected by the plasma discharge was measured.